FENOMENA ENJO KOSAI DALAM KEHIDUPAN REMAJA PUTRI JEPANG - , TIARA MUKTI HAPSARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Enjo kosai was a social phenomenon that developed around 1995 in the life ofthe Japanese people, especially in urban areas. Enjo kosai was an act often age girls around 14-19 years dating a grown man to earn some money. The purposes of writing this graduating paper are give a overview of Enjo kosai phenomenon and understanding the factors underlying the Japanese young girl did Enjo kosai. The method used by the author in this final paper is a descriptive method. Data was collected through various sources such as books, papers, journals, articles, magazines, newspapers, and the internet. The factors underlying the emergence of the phenomenon were divided into internal and external factors. First, the Japanese family structure changes that influence the position of the father and mother of the family that became the internal factor. Secondly, the external factors, including the attitude of conformity in groups of young women and the development Terekura Japan (Phone Club) on Japanese teen promiscuity. Teenage girls who did Enjo kosai mostly came from the economically capable. Thus, the economic needs is not the reason for people who did Enjo kosai.